2005
DOI: 10.1111/j.1365-2184.2005.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of stem cells with embryonic characteristics from human umbilical cord blood

Abstract: When will embryonic stem cells reach the clinic? The answer is simple -- not soon! To produce large quantities of homogeneous tissue for transplantation, without feeder layers, and with the appropriate recipient's immunological phenotype, is a significant scientific hindrance, although adult stem (ADS) cells provide an alternative, more ethically acceptable, source. The annual global 100 million human birth rate proposes umbilical cord blood (UCB) as the largest untouched stem cell source, with advantages of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
1
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(133 citation statements)
references
References 28 publications
3
121
1
8
Order By: Relevance
“…A recent study has shown that a few Oct-4 ϩ cells can be found scattered in the basal layer of the epidermis; however, the identity of these cells has not been determined (28). In contrast, a growing list of cells have been shown to express Oct-4, including cells growing in cultures from mouse bone marrow CD34 ϩ hematopoietic progenitors (29) and human umbilical cord blood (30), cultured epithelial cells lacking connexins and gap junctional intercellular communication (28), and mesenchymal stem cells (31,32). In the current study, we have demonstrated that the neonatal lung-derived Oct-4 ϩ epithelial colony cells also coexpress other stem cell markers such as SSEA-1 and Sca-1 but not c-Kit, CD34, and p63.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a few Oct-4 ϩ cells can be found scattered in the basal layer of the epidermis; however, the identity of these cells has not been determined (28). In contrast, a growing list of cells have been shown to express Oct-4, including cells growing in cultures from mouse bone marrow CD34 ϩ hematopoietic progenitors (29) and human umbilical cord blood (30), cultured epithelial cells lacking connexins and gap junctional intercellular communication (28), and mesenchymal stem cells (31,32). In the current study, we have demonstrated that the neonatal lung-derived Oct-4 ϩ epithelial colony cells also coexpress other stem cell markers such as SSEA-1 and Sca-1 but not c-Kit, CD34, and p63.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hematopoietic stem cells, cord blood contains endothelial cells, mesenchymal stromal cells, T-regulatory cells, dendritic cells, and natural killer cells [44]. These cell types can become an important area to study in medicine allowing for potentially new treatment options for additional diseases or conditions [45] including brain injury [46][47][48], strokes [47,[49][50][51]], Parkinson's [52], Alzheimer's [50,53], Huntington's [54] and amyotrophic lateral sclerosis [50,55]. Other diseases in early stages of investigation include liver disorders [56], diabetes [57,58], and myocardial infarction [49,59].…”
Section: Cord Blood Derived Stem Cells and Regenerative Medicinementioning
confidence: 99%
“…Furthermore, several groups of investigators described the presence of Oct-4 ϩ , Nanog ϩ , and SSEA-3/4 ϩ stem cells in human CB and umbilical cord matrix (Carlin et al, 2006). They were enriched by different approaches using (1) immunomagnetic beads against CD133 (Baal et al, 2004); (2) expansion of a hematopoietic cell-depleted adherent population of CB cells in the presence of thrombopoietin, kit ligand, and flt3-ligand (McGuckin et al, 2005); or (3) isolation of mononuclear cells by Ficoll gradient centrifugation (Zhao et al, 2006).…”
Section: Oct-4 ؉ Stem Cells In Cord Bloodmentioning
confidence: 99%